Genomic and antimicrobial resistance genes diversity in multidrug-resistant CTX-M-positive isolates of Escherichia coli at a health care facility in Jeddah. Issue 1 (January 2020) - Yasir, Muhammad; Farman, Muhammad; Shah, Muhammad W.; Jiman-Fatani, Asif A.; Othman, Norah A.; Almasaudi, Saad B.; Alawi, Maha; Shakil, Shazi; Al-Abdullah, Nabeela; Ismaeel, Nashat A.; Azhar, Esam I.
Abstract: Background: Whole genome sequencing has revolutionized epidemiological investigations of multidrug-resistant pathogenic bacteria worldwide. Aim of this study was to perform comprehensive characterization of ESBL-positive isolates of Escherichia coli obtained from clinical samples at the King Abdulaziz University Hospital utilizing whole genome sequencing. Methods: Isolates were identified by MALDI-TOF mass spectrometry. Genome sequencing was performed using a paired-end strategy on the MiSeq platform. Results: Nineteen isolates were clustered into different clades in a phylogenetic tree based on single nucleotide polymorphisms in core genomes. Seventeen sequence types were identified in the extended-spectrum β-lactamase (ESBL)-positive isolates, and 11 subtypes were identified based on distinct types of fim H alleles. Forty-one acquired resistance genes were found in the 19 genomes. The bla CTX-M-15 gene, which encodes ESBL, was found in 15 isolates and was the most predominant resistance gene. Other antimicrobial resistance genes (ARGs) found in the isolates were associated with resistance to tetracycline ( tet A), aminoglycoside [ aph (3″)-Ib, and aph (6)-Id], and sulfonamide ( sul 1, and sul 2). Nonsynonymous chromosomal mutations in the housekeeping genes par C and gyr A were commonly found in several genomes. Conclusion: Several other ARGs were found in CTX-M-positive E. coli isolates confer resistance to clinically important antibiotics used to treat infections caused by Gram-negative bacteria.